Adopsi dan Pemahaman Teknologi Smartwatch di Kalangan Masyarakat Desa Sembung, Wringinanom, Gresik - Rony Kriswibowo; Johan Suryo Prayogo; Danuditya Purna Atmaja; Lusi Fitria Yunani; Sayyidah Hajar Faiqotul Muhimmah; Fajar Romadhoni; Setya Budi Pratama (Pusat Riset dan Inovasi Nasional, 2025)
The development of wearable technology, especially smartwatches, opens up great opportunities in preventive health monitoring, especially in rural areas such as Sembung Village, Wringinanom, Gresik, where access to health services is limited. However, this technology is still alien to the local community. Preliminary surveys show that the majority of citizens, including health cadres, have never used or even seen a smartwatch in person, and view it as a luxury and irrelevant item. In fact, the potential of smartwatches as “digital health assistants” is huge from tracking heart rate, blood oxygen levels (SpO₂), stress levels, to physical activity reminders that are essential for early detection of health disorders. This service activity aims to improve digital literacy and adoption of smartwatch technology through a participatory educational approach and direct assistance. Implementation methods include: (1) coordination with the village government and health workers, (2) Interactive socialization using local languages, (3) step-by-step practical training, (4) simulation of application in the field, and (5) pre-test and post-test evaluation of 27 participants (25 health cadres, 1 midwife, 1 nurse). The results showed significant improvements: function understanding from the original value of 1.8 increased to 4.2, consumption interest from the original value of 2.1 increased to 4.0, benefit perception from the original value of 1.9 increased to 4.3, self confidence from the original value of 1.5 increased to 3.8, and digital literacy awareness from the original value of 2.0 increased to 4.1. The hands-on approach proved effective in changing participants ' mindset from skeptical to enthusiastic, proving that the digital divide is not due to incompetence, but the lack of access to contextual education. The implication is that smartwatch has the potential to become a strategic tool for village health cadres in early detection and real-time data-based health education, provided that it is supported by sustainable mentoring.